Intracellular distribution and internalization pathways of guanidinylated bioresponsive poly(amido amine)s in gene delivery - Jinmin Zhang; Chunxi Wang; Mei Lu; Haonan Xing; Tianzhi Yang; Cuifang Cai; Xiaoyun Zhao; Minjie Wei; Jiankun Yu; Pingtian Ding (Elsevier, 2018)
Guanidinylated bioresponsive poly(amido amine)s polymers, CAR-CBA and CHL-CBA, were synthesized by Michael-type addition reaction between guanidine hydrochloride (CAR) or chlorhexidine (CHL) and N,N'-cystaminebisacrylamide (CBA). Previous studies have shown that both polymers had high transfection efficiencies as gene delivery carriers. In this study, we investigated the nucleolus localization abilities and cellular internalization pathways of these two polymers in gene delivery. Each polymer condensed plasmid DNA (pDNA) and formed nanoparticle complexes, and then their transfection studies were performed in MCF-7 cells. Both complexes were found enriched in nucleolus after cellular transfection, and their transfection efficiencies were significantly improved when transfection was performed on MCF-7 cells arrested at M phase. The transfection efficiency of CAR-CBA-pDNA was inhibited by chlorpromazine, and cell endosomes were disrupted after being exposed to CAR-CBA-pDNA. In regards to CHL-CBA-pDNA, its transfection efficiency was not affected by three types of endocytosis inhibitors used in the study, and CHL-CBA-pDNA showed no effect on endosomes. Cellular lactate dehydrogenase release and membrane morphology were changed after cells were transfected by the two complexes. The results indicated that both CAR-CBA and CHL-CBA polymers demonstrated good nucleolus localization abilities. It was beneficial for transfection when cells were arrested at M phase. CAR-CBA-pDNA cellular internalization was involved with clathrin-mediated endocytosis pathway, and escaping from endosomal entrapment, while the cellular uptake of CHL-CBA-pDNA occurs via clathrin- and caveolae-independent mechanism. Keywords: Guanidinylated poly(amido amine)s polymers, Nucleolus localization, Cell cycle status, Internalization pathways